Validation of Educational Quality as a Tool to Measure the Degree of Satisfaction of University Students - María del Carmen Olmos-Gómez; Mónica Luque-Suárez; María Castán-García; Raquel Portillo-Sánchez (MDPI AG, 2023)
The aim of this research was the creation and validation of a questionnaire to assess education quality in university contexts and to find factors that can help improve the educational system. The questionnaire was validated via a psychometric study through exploratory (EFA) and confirmatory (CFA) data analyses from a sample of 1302 subjects to find students' level of satisfaction in the university environment. The results show good reliability and validity, highlighting three factors: access level to computer aspects; different material resources and university students' degree of satisfaction with the educational community. We concluded that this validated questionnaire provides information regarding students' opinions about the quality of education in university contexts and can serve as a measurement tool for the educational system's good functioning in an effective and efficient way.